Assessment of severity of community acquired pneumonia by paediatric infectious diseases society and clinical and radiological profile in 0-5 year age group - Shukla, Om Prakash; Rathwa, Nikunj; Mude, Lokesh Naik (International Journal of Contemporary Pediatrics, 2024)
Background: The WHO estimates that ARI, mostly in the form of CAP, is the leading cause of death in children under five, killing over 2 million children annually. The present study's PEWS score and PIDS severity criteria were undertaken to know the clinical and radiological profile of patients with Pneumonia and to categorize these patients with PEWS score and PIDS criteria to redefine their severity and assess the management and outcomes. Methods: Patients aged between 0 to 5 years who presented with cough complaints and respiration difficulty were assessed. The criteria for ICU admission is the presence of more than 2 minor criteria or one of the major criteria. PIDS criteria for CAP recommends ICU admission or continuous monitoring for children in ED. Results: A prospective observational study of 104 children with CAP was included, and their pneumonia was evaluated using PIDS criteria. The patients were categorized for pneumonia according to PIDS criteria. 32.69% of children were classified as severe CAP (p value=0.02). This difference between non-severe and severe Pneumonia is considered to be statistically significant in which patients classified as severe CAP. Conclusions: The patients were categorized for Pneumonia according to PIDS criteria. 32.69% of children were classified as severe CAP (p value=0.02). This difference between non-severe and severe Pneumonia is considered to be statistically significant in which patients classified as severe CAP needed vigorous management in emergency department followed by ICU management.